2017
DOI: 10.1590/s1806-92902017000600006
|View full text |Cite
|
Sign up to set email alerts
|

Performance, blood parameters, and carcass yield of broiler chickens supplemented with Mexican oregano oil

Abstract: -The objective of the current study was to evaluate performance, blood parameters, and carcass yield of broilers supplemented with Mexican oregano oil. A total of 162 one-day-old broilers were randomly distributed into three dietary treatments: control diet (without oregano oil or antibiotic); control diet + 0.25 g kg -1 of oxytetracycline; and control diet + 0.4 g kg -1 of Mexican oregano oil. Treatment with organ oil had positive effects on body weight at 35 and 42 days. Feed intake was significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…These results are agreement with Hong, Steiner, Aufy, and Lien (), who found that EO reduced the TC and increased HDL. Méndez Zamora, Durán Meléndez, Hume, and Silva Vázquez () found that 0.4 g EO/kg diet significantly increased TC and HDL ( p < 0.05) but did not affect TG or LDL at 42 days of age. Although the significantly reduction in LDL levels of the groups that received thyme essential oil (150 and 450 mg/kg) is evidence of the potential effect of thyme oil on the hypolipidaemic mechanism, this oil has not revealed any effect on TC, TG or HDL levels, so there is need to improve this interpretation by detailed studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results are agreement with Hong, Steiner, Aufy, and Lien (), who found that EO reduced the TC and increased HDL. Méndez Zamora, Durán Meléndez, Hume, and Silva Vázquez () found that 0.4 g EO/kg diet significantly increased TC and HDL ( p < 0.05) but did not affect TG or LDL at 42 days of age. Although the significantly reduction in LDL levels of the groups that received thyme essential oil (150 and 450 mg/kg) is evidence of the potential effect of thyme oil on the hypolipidaemic mechanism, this oil has not revealed any effect on TC, TG or HDL levels, so there is need to improve this interpretation by detailed studies.…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis (MOO treatment effects on breast meat quality are equal to the no-MOO control treatment) is based on the p-value according to a significance level determined atα = 0.05. Several studies have evaluated oregano essential oil supplementation at various levels (mg/kg) in feed: 300 (Alp et al, 2012;Skoufos et al, 2016), 65 (Bozkurt et al, 2012;Sun et al, 2015), 125 (Hong et al, 2012), 0, 60, 100 and 200 (Hashemipour et al, 2013), 15-60 (Khattak et al, 2014), 250 (Ghazi et al, 2015), 300 and 500 (Mohiti-Asli & Ghanaatparast-Rashti, 2015), 400-1600 (Silva Vazquez et al, 2015), 300 and 600 (Peng et al, 2016) and 400 (Méndez-Zamora et al, 2017). These studies obtained significant effects with all the OEO levels evaluated in broilers regarding, for example, BW, FI and FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Starter (1-21 d) and finisher (22-40 d) diets were formulated according to the NRC (1994) and as used by Silva-Vázquez et al (2015) and Méndez-Zamora et al (2017). The ingredients and analyzed chemical composition of the control starter and finisher diets are shown in Table 1.…”
Section: Birds and Experimental Dietsmentioning
confidence: 99%
See 2 more Smart Citations